Effect of privatization and inland infrastructural development on India's container port selection dynamics - Kailas Venkita Subramanian; Jean-Claude Thill (Asian Journal of Shipping and Logistics, 2019)
In this study, we present insights on how the privatization of Indian ports is altering the market share of containerized shipments across two key Industrial corridors of India. Using bill of lading dataset, we implement a binary multi-level discrete port choice model that measures the multidimensional attributes that inform the systematic differences in container shipment transport characteristics between the major government ports and private ports in India. The analysis shows that the private port of Mundra has non-trivial effects on the hinterlands of other state-owned ports. This research offers important markers of port selection in developing economies such as India. Keywords: Port Selection, Privatization, Port competition, Choice modeling, India